2010
DOI: 10.1371/journal.pone.0011352
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Embryonic Development in Mice Overexpressing the RNA-Binding Protein TIAR

Abstract: BackgroundTIA-1-related (TIAR) protein is a shuttling RNA-binding protein involved in several steps of RNA metabolism. While in the nucleus TIAR participates to alternative splicing events, in the cytoplasm TIAR acts as a translational repressor on specific transcripts such as those containing AU-Rich Elements (AREs). Due to its ability to assemble abortive pre-initiation complexes coalescing into cytoplasmic granules called stress granules, TIAR is also involved in the general translational arrest observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 43 publications
0
28
0
1
Order By: Relevance
“…1). Constitutive aggregation of intrinsic SG components has been reported to lead to a severe stall in protein synthesis and eventual apoptosis (14,20). All the HeLa/G-G3BP clones displayed uniform and high-level GFP expression, and their growth rate was comparable to that of parental cells (our unpublished observations).…”
Section: Resultsmentioning
confidence: 54%
“…1). Constitutive aggregation of intrinsic SG components has been reported to lead to a severe stall in protein synthesis and eventual apoptosis (14,20). All the HeLa/G-G3BP clones displayed uniform and high-level GFP expression, and their growth rate was comparable to that of parental cells (our unpublished observations).…”
Section: Resultsmentioning
confidence: 54%
“…Interestingly, a recent study has provided new evidence on the role of TIAR during mouse embryogenesis using an animal gain-of-function model. This report showed that TIAR controls embryo late pre-implantation stages and that its overexpression significantly impaired embryonic development beyond implantation, thereby revealing the requirement of tightly controlled TIAR expression levels for normal mouse embryo development [26]. The altered gene expression patterns associated to processes such as cell adhesion, differentiation, angiogenesis, apoptosis, proliferation and intracellular signal transduction suggest that TIA1 and TIAR play, individually and collectively, essential roles as master organizers of gene networks controlling embryonic outgrowth and patterning.…”
Section: Discussionmentioning
confidence: 82%
“…Further, these proteins seem to have an important role during embryogenesis. For example, mice lacking either TIA1 or TIAR, as well as ectopically over-expressing TIAR, show higher rates of embryonic lethality [18], [25], [26].…”
Section: Introductionmentioning
confidence: 99%
“…However, TIA-1 nullizygotes are fully fertile, whereas mice lacking the tiar gene are sterile (Beck et al 1998) due to a specific requirement for TIAR in primordial germ cell development and survival (Beck et al 1998). Moreover, overexpression of TIAR impairs embryonic development of mice at late preimplantation and post-implantation stages (Kharraz et al 2010), suggesting that balanced TIAR expression is absolutely required for early embryogenesis. The molecular mechanisms by which TIAR regulates these developmental processes are largely unknown.…”
Section: Who's On Top?mentioning
confidence: 99%